Analysis of Rectifier circuits with power factor correction - Hassan, M. M. Emran; Sultana, Afrin; Akther, Sunjida (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2014.